Tax treatment of waste and losses on income and sales tax regimes - Belito Soto, Haydee (2021)
This paper addresses fundamental notions regarding waste and losses and their treatment in both the Income Tax Law and the Peruvian General Sales Law (a.k.a. V.A.T.). Likewise, several reports issued by the Peruvian Tax Administration were used to define waste and losses and determine what may classify as deductible expenses. Finally, general aspects regarding waste and losses stipulated in the legislations of other countries are detailed in depth applying Comparative Law methods.